2012
DOI: 10.1111/j.1468-1293.2012.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and long‐term CD4 cell count trends in HIV‐positive patients with 5 years or more combination antiretroviral therapy experience

Abstract: Background The aim of this analysis is to describe the long-term changes in CD4 cell counts beyond 5 years of combination antiretroviral therapy (cART). If natural ageing leads to a long-term decline in the immune system via low-grade chronic immune activation/inflammation, then one might expect to see a greater or earlier decline in CD4 counts in older HIV-positive patients with increasing duration of cART. Methods Retrospective and prospective data were examined from long-term virologically stable HIV-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…An independent inverse association between CD4 count and ADC risk is well-established (12). In addition, evidence suggests weaker, subtler inverse associations between CD4 count and specific NADC types, especially those caused by viruses (12, 18) Furthermore, since CD4 count is correlated with long-term HIV RNA levels (41, 42), CD4 count might confound and likely mediates the association between viral suppression status and cancer risk. When we stratified by CD4 count, decreasing viral suppression IR trends persisted for all cancer and ADC within each CD4 stratum, but did not persist for virus-NADC.…”
Section: Discussionmentioning
confidence: 99%
“…An independent inverse association between CD4 count and ADC risk is well-established (12). In addition, evidence suggests weaker, subtler inverse associations between CD4 count and specific NADC types, especially those caused by viruses (12, 18) Furthermore, since CD4 count is correlated with long-term HIV RNA levels (41, 42), CD4 count might confound and likely mediates the association between viral suppression status and cancer risk. When we stratified by CD4 count, decreasing viral suppression IR trends persisted for all cancer and ADC within each CD4 stratum, but did not persist for virus-NADC.…”
Section: Discussionmentioning
confidence: 99%
“…We used the CD4/CD8 ratio after one year of virologic suppression as our primary predictor of interest rather than time-updated values in order to limit the effect of episodic HIV viremia [24]. The immune response following the first few years of ART has been shown in other studies to be a reliable reflection of changes over time during ART and has been associated with NCD outcomes [4, 49]. However, we are unable to draw conclusions about the role of time-varying changes in CD4/CD8 ratio and risk of future NCDs based upon results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have reported that the strongest predictor of long-term CD4 response is baseline CD4, even among patients with long-term HIV RNA suppression [ 8 , 11 ]. In addition, studies have found that women [ 12 ] and patients initiating treatment at younger ages [ 13 ] show better CD4 response, whereas specific cART regimens have not been shown to significantly impact long-term immune response [ 14 ]. Our results corroborate these findings.…”
Section: Discussionmentioning
confidence: 99%